The class ceiling : why it pays to be privileged / Sam Friedman and Daniel Laurison. - Friedman, Sam, 1984-; Laurison, Daniel, 1977- (Policy Press, 2019)
This important book takes readers behind the closed doors of elite employers to reveal how class affects who gets to the top. Drawing on two hundred interviews across four case studies - television, accountancy, architecture, and acting - it explores the complex barriers facing the upwardly mobile.